THE ROLE OF PATIENT SAFETY EDUCATION AND TRAINING IN IMPROVING PATIENT SAFETY - Naomi, Ruth; Bahari, Hasnah (Universitas Airlangga, 2024)
Background Patient safety education and trainings are an important element to promote patient safety culture. The demands on this training for the safety of healthcare staffs and patients are crucial due to the occurrence of preventable medical errors. These review aims to study the types of patient safety education and training that are delivered for the different target audiences as well as identifying the results of the training. Methods This study presents narrative review on literature on patient safety education and training. Peer-reviewed journals and previously published papers were searched using keywords including